Value Internalization and Character Development of Santri: A Systematic Literature Review from an Educational Psychology Perspective (Journal Of Islamic Education And Pesantren, 2025)
Islamic boarding schools (pesantren) are Islamic educational institutions that play a strategic role in shaping students’ character through a process of value internalization that is holistic, integrative, and sustainable. From the perspective of educational psychology, value internalization is understood as a psychological process in which external values are adopted into an individual’s internal value system, guiding attitudes and behaviors in a relatively stable manner. Although numerous studies have examined character education in pesantren, systematic syntheses of recent empirical findings within an educational psychology framework remain limited. This study aims to map models, strategies, and contributions of value internalization to students’ character development through a systematic literature review (SLR). The review analyzes research articles published in reputable national journals indexed by Sinta and international journals indexed by Scopus between 2019 and 2025, following stages of identification, selection, quality appraisal, and thematic analysis. The findings indicate that value internalization in pesantren is implemented through educators’ role modeling, habituation of religious routines, integration of formal and nonformal curricula, and intensive social interactions within the boarding school environment. Religiosity functions as a primary pillar of behavioral regulation, while the pesantren environment serves as a psychopedagogical ecosystem that supports comprehensive character development, including the emergence of technology-based pedagogical innovations in contemporary pesantren.